GRAPHIC DESIGN OF 100 YEAR-OLD HISTORICAL GOLDSMITH HOUSE ALONG BANG RAO NOK CANAL, BANG KRUAI DISTRICT, NONTHABURI PROVINCE - Ratchatapongton, Chalida (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The objective of this research is to 1)learn the identity of 100-year-old Historical Goldsmith House along Bang Rao Nok Canal, Bang Kruai district, Nonthaburi province, 2)learn the graphic design style that reflects the identity of 100-year-old Historical Goldsmith House, 3)evaluate the graphic design style that reflects the identity of 100-year-old Historical Goldsmith House. This is a mix methods research. The research uses both Qualitative research and Quantity research. The research is done by interview sampling. Then summarized the graphic design style and come up with a questionnaire for specialists’ evaluation and evaluation from the community and tourist. The research found that 1)the overview on identity of 100-year-old Historical Goldsmith House that considered important are the traditional architecture style of Thai house where the house has empty space under the house along the canal which is suitable for the weather with the identity of carving on the vent represents the love and relationship within the family, simple way of life with religious ceremony and good quality of life, archeological site such as temple and antique such as buddha statue, on the local natural vegetation are Freshwater mangrove along the canal. The physical appearance and concrete element as followed: alphabet carving of ส and ช which comprise of 56.66 percent, chicken carving on the vent of which comprise of 20 percent and horse carving on the vent of which comprise of 13.33 percent respectively. 2) the graphic design style that reflects the identity of 100-year-old Historical Goldsmith House, the design of symbol by using Combination Mark with the mean of 4.7, the origin of the graphic design by using Vernacular architecture and indigenous nature such as bird and club with the mean of 4.7. 3)summary of the evaluation in the graphic design style that reflects the identity of 100-year-old Historical Goldsmith House by using graphic design from the research are symbol, alphabet, graphic and color which are used for designing public relation media for community tourism, map and brochure for sightseeing within the community, environmental graphic, packaging, clothing and reusable bags found most appropriate with the mean of 4.6. The evaluation in the graphic design style that reflects the identity of 100-year-old Historical Goldsmith House together with the community and tourist found that satisfied highest at the mean of 4.83 and satisfied with overall highest at the mean of 4.77. The community is satisfied with the graphic design for community tourism because the type and style of the modern media that promote the perception and value through storytelling from design and make it easy to remember. This leads to good impression to the community where they are proud and value the traditional identity from their own cultural heritage within their community.